A systematic review and meta-analysis study to evaluate the accuracy of various PCR methods for diagnosing brucellosis in animals and humans - Muhammad Shakeel Khaliq; Muhammad Hassan Mushtaq; Abdul Rehman (Heliyon)
Brucellosis is a globally significant zoonotic disease requiring accurate and reliable diagnostic methods to enable effective control and prevention. Polymerase chain reaction (PCR) has emerged as a valuable diagnostic tool due to its high sensitivity and specificity compared to conventional methods. This study aimed to evaluate and compare the diagnostic performance of different PCR methods, including conventional PCR and real-time PCR, for brucellosis across various clinical samples, target genes, and host species. A systematic review and meta-analysis were performed in compliance with PRISMA guidelines, synthesizing data from 21 studies published from 1990 to 2022. The analysis assessed diagnostic sensitivity, analytical performance, and limits of detection for the included PCR methods. Findings revealed that real-time PCR demonstrated superior sensitivity in serum samples, while conventional PCR showed higher sensitivity in blood and aborted fetal tissues. The most frequently targeted gene was BCSP31, which consistently showed high diagnostic accuracy. Analytical specificity across all PCR methods was uniformly high, with real-time PCR demonstrating lower limits of detection, making it particularly suitable for identifying Brucella in clinical samples. In this meta-analysis, PCR demonstrates strong diagnostic accuracy for brucellosis, with high PPV and PDLR values confirming its reliability, though variability in the values highlights the need for standardized protocols to ensure consistent clinical application in both human and veterinary health settings. This study provides valuable insights into optimizing PCR diagnostic approaches for effective disease control.